1998
DOI: 10.5694/j.1326-5377.1998.tb123398.x
|View full text |Cite
|
Sign up to set email alerts
|

Home‐based treatment of cellulitis with twice‐daily cefazolin

Abstract: Objective To assess the clinical outcome and pharmacokinetics of therapy with cefazolin for patients with cellulitis in a hospital‐in‐the‐home (HIH) program. Design Observational study with outcome data compared with previously published reports of therapy for cellulitis. Setting: A university teaching hospital and HIH unit, July 1996 – December 1997. Participants Patients with cellulitis were eligible for inclusion provided their medical condition was stable, they did not require surgical intervention, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Overall, the patients treated at home spent 10.1 days in the programme, whereas the hospital patients stayed in hospital 7.4 days. Three other studies from Australia have described the results of intravenous treatment of cellulitis at home 3 4 11. Patients in these studies all needed 5.5-6.5 days of intravenous treatment at home.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the patients treated at home spent 10.1 days in the programme, whereas the hospital patients stayed in hospital 7.4 days. Three other studies from Australia have described the results of intravenous treatment of cellulitis at home 3 4 11. Patients in these studies all needed 5.5-6.5 days of intravenous treatment at home.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, outpatient parenteral antimicrobial therapy (OPAT) has gained in popularity as a cost-effective strategy for treating a variety of infectious diseases including skin and soft tissue infections 1, 2 , osteomyelitis 3, 4 , prosthetic joint infections 5 6 , and endocarditis 7 . In a 2006 survey of infectious disease physicians, 94% indicated that patients are commonly set up for OPAT at hospital discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of hospital-at-home, which originated as 'hospitalisation à domicile' in France and is now used internationally to treat patients with a variety of conditions in their home environments, [3][4][5][6][7][8][9] was taken up, as a 'winter pressures' initiative, by Hillingdon Health Authority in West London. In November 1997, the health authority commissioned Hillingdon Hospital NHS Trust with the London Borough of Hillingdon Social Services Department, and Harrow and Hillingdon Healthcare NHS Trust, to provide a rapid response hospital-at-home service.…”
Section: Introductionmentioning
confidence: 99%